Implementation of the STEM Approach in Learning and Its Relationship with Students' Critical Thinking Ability - Noni Fatillah; Zulyusri Zulyusri (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2022)
STEM is a learning approach that integrates science, technology, engineering, and mathematics. This approach was introduced by NSF (National Science, Foundation) in 1990 with the aim of forming the next generation who fulfills the abilities of the 21st century, one of which is the ability to think critically. It is important for students to develop critical thinking skills to make students think rationally in solving a problem, and collect information using examination and reasoning methods to make a decision or an action. The average level of critical thinking of students has various percentages. The purpose of this study was to examine the results of implementing the STEM approach in biology learning from 10 relevant articles and their relationship to students' critical thinking skills. The type of research used is a meta-analysis with a literature review research method using several data sources such as articles in electronic journals and books. The results showed that the application of the STEM approach influenced increasing students' critical thinking skills.